Evaluation of antidepressant-like effects of aqueous and ethanolic extracts of Pimpinella anisum fruit in mice - Zahra Shahamat; Saeid Abbasi-Maleki; Saeid Mohammadi Motamed (Mashhad University of Medical Sciences, 2016)
Objective: Pimpinella anisum (P. anisum) has different pharmacological properties such as anticonvulsant, analgesic, tranquilizer, antidepressant and anti-anxiety effects. In this study the antidepressant-like effect of aqueous and ethanolic extracts of P. anisum fruit in mice was investigated. Materials and Methods: Forced swimming test (FST) and tail suspension test (TST) were used to determine the antidepressant effects of P. anisum (50, 100 and 200 mg/kg, i.p.) fruit extracts. Fluoxetine (20 mg/kg, i.p.) and imipramine (30 mg/kg, i.p.) were used as standard drugs. Results: All the three doses of aqueous and ethanolic extracts (except 50 mg/kg of aqueous extract in FST) significantly and dose-dependently reduced the immobility times in both FST and TST. All doses of extracts increased the swimming time dose-dependently, without any significant change in climbing time. In addition, all doses of ethanolic extract reduced immobility times and increased swimming time insignificantly higher than aqueous extract. But, the two extracts decreased the duration of climbing time similarly. Fluoxetine and imipramine decreased immobility time in both tests. Fluoxetine increased the swimming time without modifying climbing time. In contrast, imipramine increased climbing time without any significant change in swimming time. Conclusion: The results of this study suggest that P. anisum possesses an antidepressant-like activity similar to that of fluoxetine, which has a potential clinical value for application in the management of depression.